2020
DOI: 10.3389/fcell.2020.00142
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NR-104098 Inhibits AML Proliferation and Induces Differentiation Through Repressing EZH2 Transcription by Interacting With E2F1

Abstract: Abundant evidence has illustrated that long non-coding RNA (lncRNA) plays a vital role in the regulation of tumor development and progression. Most lncRNAs have been proven to have biological and clinical significance in acute myeloid leukemia (AML), but further investigation remains necessary. In this study, we investigated lncRNA NR-104098 in AML and its specific mechanism. The microarray analysis was performed on NB4 cells. Based on the related analysis results, we identified that lncRNA NR-104098 is a supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 54 publications
2
40
1
Order By: Relevance
“…Our recent results show that ATPR can upregulate the expression of lncRNA NR-104098 and inhibit the differentiation and proliferation of AML induced by ATPR [11]. More in-depth mechanism studies showed that lncRNA NR-104098 played a role by enhancing the binding of E2F1 to EZH2 promoter [11]. Our results indicate that HOXA-AS2 can directly bind to EZH2 and inhibit the proliferation and induce differentiation of AML by regulating the expression of LATS2.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Our recent results show that ATPR can upregulate the expression of lncRNA NR-104098 and inhibit the differentiation and proliferation of AML induced by ATPR [11]. More in-depth mechanism studies showed that lncRNA NR-104098 played a role by enhancing the binding of E2F1 to EZH2 promoter [11]. Our results indicate that HOXA-AS2 can directly bind to EZH2 and inhibit the proliferation and induce differentiation of AML by regulating the expression of LATS2.…”
Section: Discussionmentioning
confidence: 58%
“…There are many reports that lncRNA can bind to EZH2, and then regulate the expression of downstream genes to exert its biological functions [5,33]. Our recent results show that ATPR can upregulate the expression of lncRNA NR-104098 and inhibit the differentiation and proliferation of AML induced by ATPR [11]. More in-depth mechanism studies showed that lncRNA NR-104098 played a role by enhancing the binding of E2F1 to EZH2 promoter [11].…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations